A double‐blind, placebo‐controlled, randomised, parallel‐group, dose‐escalating, repeat dose study in healthy volunteers to evaluate the safety, tolerability, pharmacodynamic effects and pharmacokinetics of the once daily rectal application of NRL001 suppositories for 14 days. (March 2014) - Bell, D.; Duffin, A.; Jacobs, A.; Pediconi, C.; Gruss, H. J.
Abstract: Aims: The 1R, 2S stereoisomer of methoxamine hydrochloride, NRL001, is a highly selective α1‐adrenoceptor agonist being developed for the local treatment of non‐structural faecal incontinence caused by weak internal anal sphincter tone. This study investigated the steady state pharmacokinetics (PK) and safety of 2 g rectal suppositories containing NRL001 in different strengths (7.5, 10, 12.5 or 15 mg). Methods: Healthy volunteers aged 18–45 years received 14 daily doses of NRL001 2 g suppositories or matching placebo. In each dose group nine participants received NRL001 and three received placebo. Blood samples to determine NRL001 concentrations were taken on Days 1, 7 and 14. Cardiovascular parameters were collected via electrocardiograms, Holter monitoring (three lead Holter monitor) and vital signs. Results: Forty‐eight volunteers were enrolled; 43 completed the study and were included in the PK analysis population. AUC and C max broadly increased with increasing dose, T max generally occurred between 4.0 and 5.0 h. Although the data did not appear strongly dose proportional, dose proportionality analysis did not provide evidence against dose proportionality as the log(dose) coefficients were not significantly < 1. NRL001 did not accumulate over time for any dose. Increasing NRL001 concentrations were related to changes in vital sign variables, most notably decreased heart rate. The most commonly reported adverse events (AEs) in the active treatment groups were paraesthesia and piloerection. Conclusions: Treatment with NRL001 was generally well tolerated over 14 days once daily dosing and plasma NRL001 did not accumulate over time. Treatment was associated with changes in vital sign variables, most notably decreased heart rate. AEs commonly reported with NRL001 treatment were events indicative of a systemic α‐adrenergic effect.